2010
DOI: 10.1159/000296504
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Health Status and Risk of Hospitalization in Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a leading cause of death and 70% of the cost of COPD is due to hospitalizations. Self-reported daily physical activity and health status have been reported as predictors of a hospitalization in COPD but are not routinely assessed. Objectives: We tested the hypothesis that self-reported daily physical activity and health status assessed by a simple question were predictors of a hospitalization in a well-characterized cohort of patients with severe emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 63 publications
3
64
0
5
Order By: Relevance
“…The extensive clinical, physiological and biological characterisation of participants within the framework of the PAC-COPD study [10] allowed the inclusion of potential confounders in the analysis, including history of previous COPD hospitalisations, which was not considered in previous studies [15,16,36]. Likewise, the use of an objective method to quantify physical activity (and the high compliance level) contrasts with previous studies that mainly used self-reported questionnaires [14,15,36,37], reduces misclassification and allows the dissection of the role of different physical activity characteristics. In theory, our results could be explained by reverse causation, i.e.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The extensive clinical, physiological and biological characterisation of participants within the framework of the PAC-COPD study [10] allowed the inclusion of potential confounders in the analysis, including history of previous COPD hospitalisations, which was not considered in previous studies [15,16,36]. Likewise, the use of an objective method to quantify physical activity (and the high compliance level) contrasts with previous studies that mainly used self-reported questionnaires [14,15,36,37], reduces misclassification and allows the dissection of the role of different physical activity characteristics. In theory, our results could be explained by reverse causation, i.e.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…На сегодняшний день взаимосвязь между уровнем регулярной ФА и частотой госпитализаций при обострениях ХОБЛ изучалось в 7 проспективных продольных исследованиях [30,113,[141][142][143][144][145] и во всех показана стабильная достоверная взаимосвязь низкой ФА с повышением риска госпитализаций. Несмотря на то, что результаты скорректированы по сопутствующим факторам, только в 1 исследовании корректировка производилась еще и по частоте предшествующих направлений в стационар по пово ду ХОБЛ, которые являются важнейшим фактором повторных госпитализаций [146].…”
Section: влияние низкой фа на частоту госпитализаций у больных хоблunclassified
“…Несмотря на то, что результаты скорректированы по сопутствующим факторам, только в 1 исследовании корректировка производилась еще и по частоте предшествующих направлений в стационар по пово ду ХОБЛ, которые являются важнейшим фактором повторных госпитализаций [146]. Продемонстриро вано, что объем регулярной ФА, необходимый для получения доказательств достоверного влияния на частоту госпитализаций у пациентов с ХОБЛ, доста точно невелик и эквивалентен ходьбе пешком или езде на велосипеде в течение 2 ч в неделю [30,113,[141][142][143][144][145].…”
Section: влияние низкой фа на частоту госпитализаций у больных хоблunclassified
“…In patients with COPD, the level of physical activity is found to be a predictor of hospital admission and mortality [44][45][46][47] . Maintaining low PA or a decrease in PA in a five year follow-up study was associated with a significant decline in health-related quality of life (HRQL) while an increase in HRQL was found in those who maintained a high level of PA 48 .…”
Section: Physical Activitymentioning
confidence: 99%